An Investigation On Stress Concentration Of Point-Fixed Bolted Glass System Subjected To Static Loading - Faisal, Farhanah (Universiti Sains Malaysia, 2018)
Bolted structural glass facades have evolved to the point where the technique appears to have matured and become the most transparent facade system available mainly for storefront, walkways and lobby areas in buildings. The point fixed glass façade system (PFGFS), also known as a spider glass system, is popular and considered to be a more elegant façade option compared to the framed glass façade system. The system is fixed to the support structure using special bolt fittings and structural spider arms, which implies that the glass must be drilled and tempered. Consequently, the glass is significantly weakened exactly at the position where peak stresses occur when forces are applied. In this research, the stress distribution on point-fixed bolted glass system subjected to static loading are investigated by means of numerical modelling and parametric analyses. A numerical model was constructed according to the specifications specified in past research project, implemented using ABAQUS software and subjected to a compressive load during three points bending test. The model was validated by comparing the past experimental results with the numerical results. By means of non-linear finite element analyses, the stress distribution of the glass panel has been investigated. The influence of the number of connectors, hole-to-edge distance, spacing of the bolt connections, hole diameter, arrangement of connectors and thickness of glass pane on stress distribution were determined through the parametric study. Increasing the number of bolts, the hole-to-edge distance, the bolt hole diameter and the glass thickness as well as the diamond pattern of bolts arrangement, have shown the positive effect on the maximum principal stress.